Simulation of the electrolyte imbalance in vanadium redox flow batteries - Baowen Zhang; Yuan Lei (PLoS ONE, 2025)
The stack is the core component of large-scale flow battery system. Based on the leakage circuit, mass and energy conservation, electrochemicals reaction in porous electrode, and also the effect of electric field on vanadium ion cross permeation in membrane, a model of kilowatt vanadium flow battery stack was established. The electro chemical reaction parameters, ion concentration and temperature of each single cell in the stack were calculated respectively. The imbalance of vanadium ion concentration and the effects of current density and electrolyte temperature on the electrolyte imbalance in the stack were studied.